Anteseden Niat Karyawan Meninggalkan Umkm dengan Persepsi Peluang Kerja Alternatif sebagai Variabel Moderasi - Mudrifah, Mudrifah (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The aim of this research is to analyze the influence of job satisfaction on organizational commitment and intention to leave MSMEs which is moderated by perceptions of alternative job opportunities. A total of 89 questionnaires were distributed to MSME employees in Malang City. The collected data was then analyzed using the descriptive-associative method with the help of PLS ​​version 3.0 software. The results of this research analysis show that job satisfaction has a significant positive influence on organizational commitment. Apart from that, job satisfaction also has a negative effect on the intention to leave the company, both directly and through organizational commitment. Perceptions of alternative job opportunities can weaken the influence of job satisfaction on organizational commitment and strengthen the negative influence of organizational commitment on intentions to leave MSMEs.